Shared bicycle microbial community: a potential antibiotic-resistant bacteria warehouse - Wu, Yuqi; Xie, Jiahui; Li, Jing; Zhao, Junyi; Qiao, Shihao; Li, Yuqing; Zeng, Jumei (Folia microbiologica, 2021)
Shared bicycle is an emerging form of public transportation in China and around the world. However, the bacterial community and drug-resistant microbiome on these bicycles have not been reported. Samples from 10 shared bicycles were observed by scanning electron microscopy (SEM). Nine samples collected from 90 shared bicycles in three different kinds of location (hospital, metro station, shopping mall) were used for full-length 16S rDNA gene analysis to figure out the bacterial composition of the shared bicycle. Samples from 32 shared bicycles were used to investigate culturable drug-resistant bacteria of the shared bicycle bacterial community. It was found that in the shared bicycle bacterial community, Bacillus was the most abundant bacteria, as determined by both SEM observation and full-length 16S rDNA gene analysis. For the analysis of drug-resistant bacteria, Bacillus showed the strongest drug resist ability. Moreover, the resistances to bacitracin and sulfamethoxazole were the most common among all types of bacteria. Our study provides an important reference for the prevention of the potential spread of drug-resistant bacteria through shared bicycles.
Keywords: Shared bicycles; Drug-resistant bacteria; mikrobiální testy citlivosti; China; Transportation; RNA, Ribosomal, 16S; Microbiota; Anti-Bacterial Agents; bakteriální léková rezistence; Public health; mikrobiota; Microbial Sensitivity Tests; cyklistika; doprava; Bacteria; Biodiversity; Čína; antibakteriální látky; Drug Resistance, Bacterial; RNA ribozomální 16S; Bicycling